IMPACT OF SMOKING ON THE SEVERITY AND OUTCOMES OF CORONAVIRUS DISEASE: A RETROSPECTIVE ANALYSIS - Mahvesh Mahmud; Muddasar Pervaiz; Shafaq Altaf; Anas Khan Channa; Mishaal Hafeez; Iqra Ibrar (Journal of Population Therapeutics and Clinical Pharmacology, 2024)
Background: The COVID-19 pandemic, caused by the novel coronavirus SARS-CoV-2, has led to global morbidity and mortality, with increasing recognition of risk factors that exacerbate disease severity. Smoking has been hypothesized to impact COVID-19 outcomes due to its known effects on the respiratory and immune systems, but evidence remains controversial.Objective: This study aimed to investigate the association between smoking and the severity of COVID-19 outcomes. Specifically, we sought to compare the clinical characteristics, disease progression, and outcomes between smokers and non-smokers diagnosed with COVID-19.Methodology: A retrospective analysis was conducted on 198 COVID-19 patients admitted to a private tertiary care hospital. Data were extracted from electronic medical records and included demographics, smoking status, comorbidities, clinical presentations, laboratory and radiological findings, disease severity, treatment modalities, and outcomes. Smokers were compared to non-smokers across various parameters. Statistical analyses were performed to determine significant differences between the two groups.Results: Among the 198 patients, 38% were smokers. Smokers had a higher mean age (52 years vs. 49 years, p=0.042) and were more likely to have comorbidities such as hypertension, diabetes, and COPD. Clinically, smokers presented with more severe respiratory symptoms, higher inflammatory markers, and greater radiological lung involvement. Smokers were more likely to progress to severe COVID-19, requiring ICU admission (50.7% vs. 17.9%, p